Localización cromosómica de genes ribosomales activos en Phyllomedusa hypochondrialis y P. Sauvagii (Anura: hylidae) - Morand, Mariana (1997)
The chromosomes of Phyllomedusa sauvagii and P. hypochondrialis were studied. Metaphases were obtained from bone narrow and intestinal epithelial cells and the activity of nucleolar organizer regions (NORs) were detected using silver banding techniques. Differences in number and NOR location between the species and heteromorphism in P. hypochondrialis are described.